Development and validation of a patient‐reported disability measurement tool for patients with inflammatory bowel disease. Issue 4 (22nd December 2012) - Allen, P. B.; Kamm, M. A.; Peyrin‐Biroulet, L.; Studd, C.; Mc Dowell, C.; Allen, B. C. M.; Connell, W. R.; De, P. P.; Bell, S. J.; Elliot, R. P.; Brown, S.; Desmond, P. V.; et al.
Summary Background Inflammatory bowel disease can impact on a patient's ability to maintain normal physical and mental function, and fulfil their social, family and work roles. Aspects of disability in IBD have received little attention. Aim To develop, validate and apply a questionnaire directed towards evaluating these disease aspects. Methods A literature review on disability in IBD was undertaken, and opinion about aspects of disability to measure was sought from six IBD‐specialised gastroenterologists. A questionnaire was developed, and IBD patients completed the new disability questionnaire, the SF‐36 and the short‐IBD (SIBDQ ‐ 10 point). A subgroup of patients completed the questionnaire again 4 weeks later. Healthy volunteers were studied as a control group. Results A total of 116 IBD out‐patients were approached, of whom 81 (52 Crohn's disease and 28 ulcerative colitis) participated. Nineteen patients were re‐evaluated at 4 weeks. Twenty‐five controls were studied. All subscales demonstrated good Cronbach's alpha reliability and reproducibility. There was a significant inverse correlation between the disability score and the SIBDQ and between the disability score and the SF36 and a positive correlation with the Crohn's Disease Activity Index (CDAI) (all P < 0.001). Disability differed between ulcerative colitis and controls, but not between active and inactive disease. Conclusions The new disability questionnaire is sensitive for detecting disability, is reliable and reproducible, and correlates with disease activity in Crohn's disease, but not ulcerative colitis. Further prospective testing is now needed in the longer term, larger patient populations and in different countries and ethnicities.